Sustainable Purchasing Trends Among Gen-Z: Understanding Through Online Media - Nata Rosalia; Muhammad Aris Syafi; Hendri Hermawan Adinugraha (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2025)
This study discusses sustainable purchasing trends among Generation Z influenced by online media such as social media, blogs, and marketplaces.  Generation-Z has a high awareness of sustainability and chooses ethical and environmentally friendly products. They are exposed to various content    that    introduces sustainable    products through influencers and online communities, which shapes their awareness and consumption choices.  This study uses qualitative methods, involving in-depth interviews, participant observation, and documentation to understand the    sustainable    consumption    behavior    of Gen-Z    in Wonokerto District.  The findings show that online media plays a major role in increasing sustainability awareness and influencing product preferences among Gen-Z.  This study offers   insights   for   industry players to design   effective marketing   strategies   and for policymakers to promote sustainable consumption.